2002
DOI: 10.2169/internalmedicine.41.309
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary MALT Lymphoma with Amyloid Production in a Patient with Primary Sioegren's Syndrome.

Abstract: A 53-year-old womanwasadmitted to our hospital complaining of cough, low grade fever, chest pain and sicca symptoms. A chest radiograph showed an abnormal shadow and chest computed tomography revealed a tumor in left S6. She was diagnosed as Sjogren's syndrome by sialography and histological findings of labial biopsy. The surgically resected tumor specimen showed proliferation of lymphoid cells with lymphoepithelial lesions, which were positive for CD20 and kappa light chain. Kappa light chainpositive amyloid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…It is therefore very important to evaluate the histological classification of the lung in PSS [15,16,17]. However, the histopathologic pulmonary manifestations of PSS are not well defined in the literature [5,18,19,20,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore very important to evaluate the histological classification of the lung in PSS [15,16,17]. However, the histopathologic pulmonary manifestations of PSS are not well defined in the literature [5,18,19,20,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Although nodular lesions are very uncommon in pulmonary AL amyloidosis, Rajagopala et al [10] pointed out the relationship between pulmonary AL amyloidosis and Sjögren's syndrome. Nakamura et al [11] and Satani et al [12] also reported on the combination of Sjögren's syndrome and pulmonary mucosaassociated lymphoid tissue (MALT) lymphoma. We cannot determine the precise relationship between the unique pathological features found on renal biopsy and pulmonary limited AL amyloidosis in the present case, which showed no evidence of Sjögren's syndrome or MALT lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Amyloidosis is also associated with systemic lymphoproliferative disorders and plasma cell dyscrasias (2,5,6 (8). MALT lymphoma sometimes may contain amyloid deposits, but this finding is extremely rare; it has been reported in only 18 cases (3,6,(8)(9)(10)(11)(12)(13)(14). This report presents a case of pulmonary AA (amyloid-associated) type amyloidosis with cyst-like structures and MALT lymphoma coexisting independently in the left upper lobe.…”
Section: Amyloid Is a Pathological Fibrillar Proteinaceous Substancementioning
confidence: 93%
“…Cyst-like lesions corresponded to dilated bronchioles infiltrated by amyloidosis (Fig. 2f) (3,6,(8)(9)(10)(11)(12)(13)(14), (4,12,13). MALT of the stomach is considered to be associated with a continuous infection of Helicobactor pylori.…”
Section: Amyloid Is a Pathological Fibrillar Proteinaceous Substancementioning
confidence: 99%